Estimated Absorbed Zinc Intake Is Low in Breastfed 6–11.9 Month Old Infants: Data From the Feeding Infants and Toddlers (FITS) Study, 2016. (7th June 2021) - Finn, Kristen; Hampton, Joel; Abrams, Steven
Abstract: Objectives: To calculate daily absorbed zinc (Zn) intakes, evaluate and rank dietary Zn sources, and assess the percentage of 6–11.9 month old breastfed, mixed fed, and formula fed infants at risk for inadequate absorbed Zn based on their intake and dietary Zn sources. Methods: FITS is a cross-sectional dietary survey of children aged 0–47.9 months in the U.S. For this analysis, Zn absorption factors utilized in the Dietary Reference Intake (DRI) methodology (50% for human milk, 30% for all other sources) were applied to all food sources of Zn in the 24 hour dietary recall for 6–11.9 month old infants (n = 902). The estimated amount of Zn in human milk (0.83μg/ml) and the absorbed Zn requirement for 6–12 month old infants (836μg/day) were based on DRI methodology. Dietary Zn sources were ranked according to contribution to total calculated absorbed Zn. Differences in calculated mean absorbed Zn intakes and the percentage of infants falling below the daily absorbed zinc requirement among breastfed (n = 296), mixed fed (n = 102), and formula fed infants (n = 448) were assessed by unpaired t-tests. Results: Among 6–8.9 month old breastfed infants, the mean absorbed Zn (0.58 μg/day) and percentage of infants falling below the daily dietary intake requirement (90.9%) were significantly different than mixed fed, (1.32μg/day and 14.5% below) or formula fed infants (2.17μg/day and 0.1% below, p < 0.0001 for all comparisons). Among 9–11.9 month old infants, the mean absorbed Zn intakes and percentage of infants falling below the daily requirement improved, but remained significantly different across all feeding types (1.00 μg/day and 33.4% of infants below in breastfed, 1.33μg/day and 13.8% below in mixed fed, 2.41μg/day and 0.0% below in formula fed, p < 0.0001 for all comparisons except difference in means for breastfed vs. mixed fed p = 0.0011). The primary sources of calculated absorbed Zn were human milk or infant formula followed by infant cereal and then meat. Conclusions: Using established factors to account for bioavailability of dietary Zn sources, the majority of breastfed older infants are at risk for inadequate Zn intake, especially during the initial time of introduction of solid foods. Focusing on high Zn containing intake, including meat and fortified cereals may be important to assure adequate Zn intake. Funding Sources: Nestlé Research, Switzerland and Nestlé Nutrition, Arlington, VA.